Congenital Absence of Tracheal or Bronchial Rings. (25th August 2020) - Smith, Matthew M.; Kou, Yann‐Fuu; Schweiger, Claudia; Lehenbauer, David G.; de Alarcon, Alessandro; Rutter, Michael J.
Abstract : Objective: Congenital airway stenosis secondary to absent tracheal or bronchial rings is a rare congenital anomaly that is difficult to manage both clinically and surgically. This typically manifests as severe segmental tracheomalacia, and only isolated cases with short‐term follow‐up have been previously described. We aim to describe a series of children with absent tracheal or bronchial rings who underwent surgical management and had long‐term follow‐up. Study Design: Case series with chart review. Setting: Tertiary care pediatric hospital. Methods: Patients with absent tracheal or bronchial rings from 2002 to 2016. Electronic and paper medical records were queried to obtain demographics, age at diagnosis and surgery, pre‐ and postoperative symptoms, location of absent rings, procedure performed, length of follow‐up, and adjunctive procedures performed. Results: Nine subjects were identified who underwent slide tracheoplasty for correction of congenital absent tracheal or bronchial rings. Age at diagnosis ranged from 10 days to 5 years of age (median, 4 weeks). Age at surgery ranged from 3 weeks to 5 years of age (median, 5 weeks). Six out of 9 subjects were extubated on postoperative day 1. Only 1 subject required additional intervention, which included balloon dilation, tracheobronchial stenting, and aortopexy to alleviate the obstruction. Mean follow‐up time was 5.89 years. Conclusions: This is the largest series of children with absent tracheal rings who underwent slide tracheoplasty with long‐term follow‐up presented to date. Slide tracheoplasty is an effective surgical intervention for the treatment of absent tracheal or bronchial rings in infants and young children.